PERBEDAAN TINGKAT NYERI HAID SEBELUM DAN SESUDAH DILAKUKAN SENAM DISMENORE PRIMER PADA SISWI KELAS X DI SMK NEGERI 5 SINGKAWANG - ., Dana Chrisdayanti (Universitas Tanjungpura, 2015)
Background: The major complaint which is often felt by many women, who are in their menstrual cycles, is menstrual pain (dysmenorrhea). In Indonesia, it is estimated as many as 55% of women in their productive age experience dysmenorrhea. Primary dysmenorrhea is common in ages 12 to 25 and often occurs about 2 to 3 years after menarche. In general, 50-60% of women would rather use analgesics to manage dysmenorrhea than using nonpharmacology approaches. Intervention with pharmacological approaches can cause a dangerous side effect and dependence if taken for a long time. To avoid this, it would be much better if the young women use a nonpharmacology intervention for menstrual pain. One of many nonpharmacology therapies they can try is primary dysmenorrhea exercise. Objective: To identify the difference of menstrual pain level before and after primary dysmenorrhea exercise on tenth graders in SMK Negeri 5 Singkawang. Methodology: This is a quantitative study, uses quasi experimental design with pre and post-test design without control. The sampling technique uses purposive sampling with total sample 26 respondents. Assessment of the level menstrual pain using a verbal descriptive scale for comparing the level of menstrual pain before and after primary dysmenorrhea exercise. For statistic test, this study uses the Wilcoxon test because data distribution is not normal. Results: The mean level of menstrual pain pretest is 1.77 and the mean level of menstrual pain posttest is 0.73. The statistical test of Wilcoxon results p value = 0.000 (p 0.005). Conclusion: There are differences in the level of menstrual pain before and after exercise primary dysmenorrhea on tenth graders in SMK Negeri 5 Singkawang. Keywords: teenage girl, menstrual pain level, primary dysmenorrhea exercise References: 62 (2001-2015)